2022
DOI: 10.1155/2022/4631983
|View full text |Cite
|
Sign up to set email alerts
|

Antidyslipidemic, Antioxidant, and Anti-inflammatory Effects of Jelly Drink Containing Polyphenol-Rich Roselle Calyces Extract and Passion Fruit Juice with Pulp in Adults with Dyslipidemia: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Oxidative stress and inflammation play key roles in the pathophysiology in the pathophysiology of dyslipidemia, which are positive risks that increase atherosclerosis leading to important healthcare problems. Therefore, we aimed to study the antioxidant, anti-inflammatory, and lipid-lowering effects of jelly drink containing polyphenol-rich roselle calyces extract and passion fruit juice with pulp concentrate (RP jelly drink) in comparison to a placebo jelly drink for 8 weeks. Forty-three adults with dyslipide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 57 publications
0
23
0
3
Order By: Relevance
“…Outro composto citado é o maracujá (Passiflora edulis), uma fruta que possui em sua composição polifenóis, flavonóides, alcalóides, carotenóides e ácido ascórbico, os quais possuem efeitos antioxidantes, anti-hipertensivos, antitumorais, hipolipidêmicos e antiinflamatórios (KHONGRUM et al, 2022).…”
Section: Maki Et Al 2022unclassified
See 1 more Smart Citation
“…Outro composto citado é o maracujá (Passiflora edulis), uma fruta que possui em sua composição polifenóis, flavonóides, alcalóides, carotenóides e ácido ascórbico, os quais possuem efeitos antioxidantes, anti-hipertensivos, antitumorais, hipolipidêmicos e antiinflamatórios (KHONGRUM et al, 2022).…”
Section: Maki Et Al 2022unclassified
“…Em relação ao campo científico, não existem ainda relatos sobre a eficácia de uma combinação de extrato de cálice de rosela e componentes bioativos de maracujá em alimentos funcionais sobre a melhora do quadro de hipolipidemia. Diante disso, um estudo randomizado buscou avaliar os efeitos hipolipidêmicos, antioxidantes e anti-inflamatórios da bebida gelatinosa composta por extrato de cálices de rosela rico em polifenóis e suco de maracujá com polpa, sendo ingerida repetidamente durante 8 semanas entre adultos hiperlipidêmicos (KHONGRUM et al, 2022).…”
Section: Maki Et Al 2022unclassified
“…MDA, an oxidative marker of lipid peroxidation, correlates with the level of serum total cholesterol, triglyceride (TG), and LDL cholesterol [ 87 ], and extract leaves and calyces of roselle were proven to inhibit lipid peroxidation in vitro [ 76 ]. Moreover, atherosclerotic rabbit models that were fed delphinidin-3- O -glucoside from roselle in doses of 10 and 20 mg/kg for 12 weeks showed inhibited oxidative stress via the upregulation of GSH-PX and SOD1 mRNA levels [ 88 ].…”
Section: Roselle In the Attenuation Of Cardiovascular Diseases Risk F...mentioning
confidence: 99%
“…Previously, a study that was conducted by Asgary et al [ 105 ] in a double-blind placebo-controlled clinical trial showed that the daily consumption of 500 mg of roselle calyx powder for 4 weeks among forty adult patients with metabolic syndrome (hypertension, dyslipidemia, hyperglycemia) was able to significantly reduce serum TG and systolic blood pressure. Continuing with another randomized, double-blind, placebo-controlled trial, 300 mL of jelly drink containing polyphenol-rich roselle calyx extract given to forty-three adults with dyslipidemia for 8 weeks was demonstrated to decrease the levels of LDL-C, TG, TNFα, and MDA, and enhance the GSH level [ 87 ]. Hence, this study proved that roselle consumption could prevent CVD due to its polyphenolic content by exerting antioxidant and anti-inflammatory effects.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…This compound is a powerful free radical scavenger with inhibiting glycation and scavenging activity against DPPH and superoxide anions thereby increasing antioxidant activity or reducing ROS to detoxify oxidative damage (Jin et al, 2022). Roselle can also be further studied as a pharmacological treatment to reduce risk factors for cardiovascular disease because it has been proven to have antihyperlipidemic, antihyperglycemic, antioxidant, antiinflammatory, antihypertensive, and antifibrosis properties (Ratna et al, 2018;Jamrozik, Borymska & Kaczmarczyk-Żebrowska, 2022;Khongrum et al, 2022;Sapian et al, 2023). Therefore, we want to relate and discuss in depth the potential use of Rosella in reducing oxidative stress and inflammation after physical activity through a systematic review.…”
Section: Introductionmentioning
confidence: 99%